The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jmg.12486
|View full text |Cite
|
Sign up to set email alerts
|

Testing the fidelity of thermometers at ultrahigh temperatures

Abstract: A highly residual granulite facies rock (sample RG07‐21) from Lunnyj Island in the Rauer Group, East Antarctica, presents an opportunity to compare different approaches to constraining peak temperature in high‐grade metamorphic rocks. Sample RG07‐21 is a coarse‐grained pelitic migmatite composed of abundant garnet and orthopyroxene along with quartz, biotite, cordierite, and plagioclase with accessory rutile, ilmenite, zircon, and monazite. The inferred sequence of mineral growth is consistent with a clockwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…(c) The trace element thermometers such as Ti–in–zircon (Ferry & Watson, ) and Zr‐in‐rutile (Ferry & Watson, ; Tomkins, Powell, & Ellis, ) strongly correlate with textural occurrence of zircon and rutile and occasionally yield UHT conditions for some granulites (e.g. Ague, Eckert, Chu, Baxter, & Chamberlain, ; Clark et al, ; Liu, Li, & Santosh, ). (d) The Al‐in‐orthopyroxene thermometer can provide reliable estimates of peak conditions in Al‐saturated rocks (Clark et al, ; Harley & Motoyoshi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) The trace element thermometers such as Ti–in–zircon (Ferry & Watson, ) and Zr‐in‐rutile (Ferry & Watson, ; Tomkins, Powell, & Ellis, ) strongly correlate with textural occurrence of zircon and rutile and occasionally yield UHT conditions for some granulites (e.g. Ague, Eckert, Chu, Baxter, & Chamberlain, ; Clark et al, ; Liu, Li, & Santosh, ). (d) The Al‐in‐orthopyroxene thermometer can provide reliable estimates of peak conditions in Al‐saturated rocks (Clark et al, ; Harley & Motoyoshi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ague, Eckert, Chu, Baxter, & Chamberlain, ; Clark et al, ; Liu, Li, & Santosh, ). (d) The Al‐in‐orthopyroxene thermometer can provide reliable estimates of peak conditions in Al‐saturated rocks (Clark et al, ; Harley & Motoyoshi, ). Moreover, the contents of grossular in garnet and anorthite in plagioclase in P–T pseudosections have much higher potentials for recording UHT conditions than other elements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Clark et al. (2019) attempted to estimate the peak metamorphic condition from a highly residual granulite facies migmatitic rock from Lunnyy Island in the Rauer Group, East Antarctica, using multiple thermobarometric approaches. A clockwise P–T path was inferred from sequence of mineral growth with a phase equilibria modelling for the whole‐rock chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium-in-zircon thermometry has been used widely to estimate peak conditions in granulites and UHT granulites, but temperature results commonly fall on the retrograde path (e.g., Baldwin et al, 2007;Ewing et al, 2013;Kelsey and Hand, 2015;Clark et al, 2019). Clark et al (2019) reported that Ti-in-zircon thermometry applied to granulites from East Antarctica returned temperatures ~70-230 °C lower than estimated peak temperatures of 910 ± 50 °C based on Al-in-orthopyroxene thermobarometry, Zr-inrutile thermometry, and phase equilibria modeling combined with calculated compositional isopleths.…”
Section: Titanium-in-zircon Thermometrymentioning
confidence: 99%
“…Titanium-in-zircon thermometry has been used widely to estimate peak conditions in granulites and UHT granulites, but temperature results commonly fall on the retrograde path (e.g., Baldwin et al, 2007;Ewing et al, 2013;Kelsey and Hand, 2015;Clark et al, 2019). Clark et al (2019) reported that Ti-in-zircon thermometry applied to granulites from East Antarctica returned temperatures ~70-230 °C lower than estimated peak temperatures of 910 ± 50 °C based on Al-in-orthopyroxene thermobarometry, Zr-inrutile thermometry, and phase equilibria modeling combined with calculated compositional isopleths. Several studies of UHT granulites show that zircon crystallization takes place on the retrograde cooling path, resulting in Ti-in-zircon temperatures below peak conditions as documented by phase equilibrium modeling, Zr-in-rutile thermometry, and reaction microtextures between sapphirine and quartz, for example (Baldwin et al, 2007;Ewing et al, 2013;Kelsey and Hand, 2015;Clark et al, 2019).…”
Section: Titanium-in-zircon Thermometrymentioning
confidence: 99%